Hak dan Kewajiban Warga Negara dalam Pandangan Mahasiswa di Universitas Negeri Medan - Naulita Panggabean, Jamaludin, Bartolomeus Simanjorang, Lennai Situmorang, (Pusdikra Publishing, 2023)
Every human being must understand his existence as the most noble creature created by God, whose rights as a human being must be fulfilled, for example freedom from oppression and slavery. Humans must also not forget their obligations. The research method used is a qualitative research method with a descriptive approach. Where the researcher took several respondents to give a questionnaire containing questions about rights and obligations. The aim of this research is to see the extent to which Medan State University students understand the rights and obligations of citizens. Rights and obligations must continue to go hand in hand and remain balanced in the life of the nation and state in order to create a safe, prosperous, safe and prosperous society.